Politics and IMF Conditionality - Axel Dreher; Jan-Egbert Sturm; James Raymond Vreeland (Center for Economic Studies and ifo Institute (CESifo), 2013)
Bailouts sponsored by the International Monetary Fund (IMF) are famous for their conditionality: in return for continued installments of desperately needed loans, governments must comply with austere policy changes. Many have suggested, however, that politically important countries face rather weak stringency. Obstacles to testing this hypothesis include finding a measure of political importance that is not plagued by endogeneity and obtaining data on IMF conditionality. We propose to measure political importance using temporary membership on the United Nations Security Council and analyze a newly available dataset on the level of conditionality attached to (a maximum of) 314 IMF arrangements with 101 countries over the 1992 to 2008 period. We find a negative relationship: Security Council members receive about 30 percent fewer conditions. This suggests that the major shareholders of the IMF trade softer conditionality in return for political influence over the Security Council.
Keywords: O19; O11; F35; 330; IMF; UN Security Council; voting; aid; conditionality